Eksekusi Iklan Televisi dengan Pendekatan Parodi - Tinarbuko, Sumbo (FISIP Universitas Atma Jaya Yogyakarta, 2007)
Abstract: The use of the parody approach in designing publicity could be developped further, thus the information and the message carried in an advertisement would not appear as a form of indoctrination with the adequate use of parody, the tergetted customer will feel entertained.